Progressive Muscle Relaxation Increase Peak Expiratory Flow Rate On Chronic Obstructive Pulmonary Disease Patients - Tintin Sukartini; Ika Yuni Widyawati; Yani Indah Sari (Jurnal Ners, 2008)
Introduction: Limited progressive air flow in Chronic Obstructive Pulmonary Disease (COPD) can caused by small airway disease (bronchiolitis obstructive) and loss of elasticity of the lung (emphysema). Further it can be decreasing the quality of life in COPD patients because dyspnea and uncomfortable in activity. Progressive muscle relaxation (PMR) is one of the relaxation technique that can repair pulmonary ventilation by decreasing chronic constriction of the respiratory muscles. The objective of this study was to analyze the effect of progressive muscle relaxation on raised peak expiratory flow rate (PEFR).Methods: A pre-experimental one group pre-post test design was used in this study. Population was all of the COPD patients at Pulmonary Specialist Polyclinic Dr Mohamad Soewandhie Surabaya. There were 8 respondents taken by using purposive sampling. PEFR was counted by using peak flow meter every six day. Data were analyzed by using Paired t-Test with significance level  p≤0.05.Results: The result showed that PMR had significance level on increasing of PEFR (p=0.012).Conclusion: It can be concluded that PMR has an effect on raise PEFR. Further studies are recommended to measure the effect of PMR on respiratory rate (RR), heart rate (HR) subjective dyspnoe symptoms, forced expiration volume on the first minute (FEV1) and mid maximum flow rate (MMFR) in COPD patients.